Technical and Legal Implications for Dynamic Legalities: How Can the BBNJ Treaty Accommodate Dynamic Management Decision-Making for Arctic MPAs? - Fisher, Andrea M. (UiT Norges arktiske universitet, 2021)
The Central Arctic Ocean (Central AO) is rapidly changing. Climate change is resulting in declining sea-ice extent and thickness, ecosystem restructuring, and new opportunities for human activities. Marine protected areas (MPAs) for the Arctic high seas will need to be adaptive and flexible to respond to the complex and dynamic system. Dynamic Ocean Management (DOM), a novel approach where management measures change in near real-time based on new ocean data, could be applied for a more effective response than typical static MPAs. This research considers how decision-making for a DOM approach to Arctic MPAs can be accommodated in the treaty that is being negotiated for the conservation and sustainable use of marine biological diversity in areas beyond national jurisdiction (BBNJ). Accommodation of a DOM approach would help 'future-proof' the BBNJ treaty for climate change and new ocean challenges. However, legal concerns regarding near real-time adjustments to measures and boundaries of protected areas will need to be addressed.